Presentation of Neutralizing Antibodies in Single- or Pooled-Convalescent Immune Plasma from Donors to Prevent the Current SARS-CoV-2 Pandemic - Fatih Ozcelik; Muhterem Ercan; Bulent Barıs Guven; Mehmet Zahit Ciraci (International Journal of Coronaviruses, 2020)
As there is no specific treatment yet, the fight against the COVID-19 pandemic is being carried out with great difficulty today. The use of immune plasma is seen as a promising option since there is expectation that it will reduce mortality, as in influenza pandemics experienced in 1918 and 2009. However, the safety and effectiveness of this treatment option against SARS-CoV-2 viruses are not known for certain. In addition, the optimal obtaining methods and protection time of neutralizing antibodies to be used to provide passive immunization are not fully known. Therefore, it would be very useful to investigate the most effective neutralizing antibody collection methods without disrupting the overall structure and effectiveness of the antibodies subject to the use of the convalescent immune plasma. For this purpose, we found it appropriate to prepare a broad review on the structure and properties of antibodies, as well as the principles and storage conditions of antibodies to be used in passive immunization.
Keywords: Convalescent Immune Plasma